1993
DOI: 10.1149/1.2220748
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolyzed Cobalt Phthalocyanine as Electrocatalyst for Oxygen Reduction

Abstract: Cobalt phthalocyanine (CoPc) adsorbed on carbon black (Vulcan XC-72) and heat-treated at temperatures ranging from 300 to 1150~ display catalytic activity toward the electroreduction of oxygen in acidic medium (H2SO4, pH 0.5). The best catalysts are obtained for pyrolysis temperatures ranging from 700 to 950~ X-ray diffraction performed on CoPc/XC-72 pyrolyzed between 700 and 1150~ reveals the presence of B-Co particles whose average size varies from 9 nm at 700~ to 44 nm at 1150~ Co and N bulk elemental analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(81 citation statements)
references
References 6 publications
(6 reference statements)
8
70
0
3
Order By: Relevance
“…These catalysts suffered from low ORR activity and stability in the ORR regime and are, thus, far from satisfying the requirements for their application in commercial fuel cells. Subsequently, in the 1970s, pyrolysis of metal-N 4 macrocycles adsorbed on carbon black in inert atmosphere was discovered to significantly improve the ORR activity as well as the stability [12][13][14][15][16][17] of the catalyst. It is proposed in the literature that, upon pyrolysis, the metal-N4 macrocycle molecules decompose, resulting in the catalysts containing the M-N 4 type of active sites to be embedded on the carbon support [18].…”
Section: Mnc-based Catalyst Obtained Through Pyrolysismentioning
confidence: 99%
“…These catalysts suffered from low ORR activity and stability in the ORR regime and are, thus, far from satisfying the requirements for their application in commercial fuel cells. Subsequently, in the 1970s, pyrolysis of metal-N 4 macrocycles adsorbed on carbon black in inert atmosphere was discovered to significantly improve the ORR activity as well as the stability [12][13][14][15][16][17] of the catalyst. It is proposed in the literature that, upon pyrolysis, the metal-N4 macrocycle molecules decompose, resulting in the catalysts containing the M-N 4 type of active sites to be embedded on the carbon support [18].…”
Section: Mnc-based Catalyst Obtained Through Pyrolysismentioning
confidence: 99%
“…The difference in the characteristics between NSCC and N 4 -M catalysts are as follows: (1) The ORR activity of N 4 -M catalysts diminishes by acid leaching; however, the ORR activity of NSCC is maintained or increased by the same treatment. 29,30 (2) Both N and metal species are required for the preparation of N 4 -M; however, they are not required for the preparation of NSCC. 31,32 (3) The formation of an NS structure inhibits ORR activity in the case of N 4 -M catalysts; however, ORR activity is not inhibited in the case of NSCC.…”
Section: Bn-doped Carbon Alloy Catalystsmentioning
confidence: 99%
“…The most active CoPc/C catalyst for ORR was obtained after pyrolysis at 600°C under an inert atmosphere for 2 h [94]. Detailed studies [95,96] showed that the SIMS intensities of Co ? and all other Co-containing organic fragments decreased with increasing pyrolysis temperature.…”
Section: Heat Treatmentmentioning
confidence: 99%
“…The formation of Co metal and/or Co-containing fragments was responsible for catalytic activity enhancement in the temperature range of 600-700°C. Ladouceur et al [95] investigated the influence of pyrolysis temperature on the electrocatalysis of CoPc from 300 to 1,150°C. It was found that the best catalysts for ORR can be obtained when CoPc was pyrolyzed at a temperature ranging from 700 to 950°C.…”
Section: Heat Treatmentmentioning
confidence: 99%